Biogenic manganese oxides as reservoirs of organic carbon and proteins in terrestrial and marine environments. Issue 1 (11th July 2016) - Estes, E. R.; Andeer, P. F.; Nordlund, D.; Wankel, S. D.; Hansel, C. M.
Abstract: Manganese (Mn) oxides participate in a range of interactions with organic carbon (OC) that can lead to either carbon degradation or preservation. Here, we examine the abundance and composition of OC associated with biogenic and environmental Mn oxides to elucidate the role of Mn oxides as a reservoir for carbon and their potential for selective partitioning of particular carbon species. Mn oxides precipitated in natural brackish waters and by Mn(II)‐oxidizing marine bacteria and terrestrial fungi harbor considerable levels of organic carbon (4.1–17.0 mol OC per kg mineral) compared to ferromanganese cave deposits which contain 1–2 orders of magnitude lower OC. Spectroscopic analyses indicate that the chemical composition of Mn oxide‐associated OC from microbial cultures is homogeneous with bacterial Mn oxides hosting primarily proteinaceous carbon and fungal Mn oxides containing both protein‐ and lipopolysaccharide‐like carbon. The bacterial Mn oxide‐hosted proteins are involved in both Mn(II) oxidation and metal binding by these bacterial species and could be involved in the mineral nucleation process as well. By comparison, the composition of OC associated with Mn oxides formed in natural settings (brackish waters and particularly in cave ferromanganese rock coatings) is more spatially and chemically heterogeneous. Cave Mn oxide‐associated organic material is enriched in aliphatic C, which together with the lower carbon concentrations, points to more extensive microbial or mineral processing of carbon in this system relative to the other systems examined in this study, and as would be expected in oligotrophic cave environments. This study highlights Mn oxides as a reservoir for carbon in varied environments. The presence and in some cases dominance of proteinaceous carbon within the biogenic and natural Mn oxides may contribute to preferential preservation of proteins in sediments and dominance of protein‐dependent metabolisms in the subsurface biosphere.